Petanque Shot Dynamics: Effect of Swing Angle, Speed, and Release Angle at Distances of 6,7,8,9 Meters - Nurkholis, Nurkholis (Proceeding of International Joint Conference on UNESA, 2025)
This study is supposed to analyze the influence of swing angle, movement speed, and release angle on shooting dynamics at 6, 7, 8, and 9 meters in petanque sport. This study used a non-experimental method with quantitative descriptive approach, on 45 male shooting players at PON XXI pre-qualification national championship. Data were collected utilizing Kinovea software and descriptive and inferential statistical test (bivariate correlation). The results revealed that swing angle back, swing speed, and release angle together accounted for most of the shot outcome at all distances. The efficacy of shooting techniques in reducing distance, with maximum contribution at a distance of 7 meters (R Square 0.920) and minimum at a distance of 8 meters (R Square 0.556). The swing speed and back swing angle are optimal at short throws (6 meters), while the release angle is relatively stable at medium throws (6-7 meters). The current study stresses the necessity for adaptive training to develop skills for acquiring back swing, swing speed, and release in order to improve petanque players' performance under varied throwing conditions.